Current sleep interventions for shift workers: a mini review to shape a new preventative, multicomponent sleep management programme - Tout, Amber F.; Tang, Nicole K. Y.; Sletten, Tracey L.; Toro, Carla T.; Kershaw, Charlotte; Meyer, Caroline; Rajaratnam, Shantha M. W.; Moukhtarian, Talar R. (Frontiers in Sleep, 2024)
Introduction. Shift work can lead to sleep disturbances and insomnia during the sleeping period, as well as excessive sleepiness and fatigue during the waking period. While Cognitive Behavioral Therapy (CBT-i) is recommended as the first line of treatment for insomnia, key elements of CBT-i, such as maintaining a consistent sleep schedule, can be challenging for shift workers, highlighting the need for tailored sleep interventions. This mini review provides a narrative synthesis of nonpharmacological sleep interventions for shift workers and informs the development of a preventative, multicomponent sleep management programme. Method. An informal review was conducted in line with Phase 1 of the Framework for the Development and Evaluation of Complex Interventions. Results. A variety of strategies have been employed to help manage the impacts of shift work on sleep, including: CBT-i, adjusting shift schedules, controlled light exposure, sleep hygiene education, planned napping, caffeine consumption, and mind-body interventions (e.g., yogic relaxation).Discussion. Recommendations, limitations, and directions for future research are discussed; notably, the role of the family, the commute to and from the workplace, and the eating behaviors of employees appear to have been overlooked in current intervention efforts. Digital CBT-i platforms could help to provide an effective, scalable, and low-cost method of reducing insomnia in shift workers.